Assignment of the Crystal Structure to the Aza-Pinacol Coupling Product by X-ray Diffraction and Density Functional Theory Modeling - Savateev, Oleksandr; Tarakina, Nadezda V.; Tyutyunnik, Alexander P.; Rivadeneira, Salvador Martinez; Heske, Julian; Kühne, Thomas D. (ACS Omega, 2022)
Aza-pinacol coupling of N-benzyl-1-phenylmethanimine using Zn dust affords a mixture of R,S-or R,R-diastereomers in a 1:1 ratio. The R,S-diastereomer is solid with an m.p. of 135 °C, while the R,R-diastereomer is liquid at room temperature. The configuration of stereocenters was determined by combining X-ray powder diffraction and density functional theory (DFT) modeling.
CRIS-Team Scopus Importer:2023-03-20